Intermediate care units in internal medicine: the case of Apulia - Francesco Ventrella; Anna Belfiore; Antonio Greco; Franco Mastroianni; Salvatore Lenti; Domenico Ruggiero; Michele Cannone; Vincenzo Ostilio Palmieri; Massimo Errico (Italian Journal of Medicine)
Recently, the growing complexity and criticality of patients hospitalized in internal medicine have highlighted the inadequacy of the traditional model based on the “average” standard of care provided to all patients. In this context, intermediate care units (IMCUs) integrated into internal medicine departments have become essential for the management of patients who need a higher level of care than standard patients without requiring intensive care assistance. In Italy, the role of IMCUs in internal medicine was highlighted during the COVID-19 pandemic when many internal medicine units were transformed into COVID areas at different levels of intensity of care. Patients with respiratory failure requiring non-invasive ventilation were managed at the IMCUs coordinated by internal medicine specialists. In Apulia, the debate on the reorganization of internal medicine began many years before the pandemic. In 2012, the regional section of FADOI (Federation of Associations of Hospital Doctors on Internal Medicine) and SIMI (Italian Society of Internal Medicine) had already developed and presented to the regional health department a project for the Apulian internal medicine network in terms of intensity of care. It was only after the COVID-19 pandemic, which involved several internal medicine departments in the region, that the health authorities accepted the proposal to reorganize internal medicine. The Regional Council Resolution No. 1710 of 11/29/2023, Apulia region, ruled in favor of the opening of the IMCUs in internal medicine. Several internal medicine units in the region have adopted this measure, responding to the needs of modern internal medicine.